POROSITAS MIKROSTRUKTUR SILIKA KERAMIK HASIL EKSTRAKSI DARI LIMBAH SEKAM PADI YANG DISINTERING DENGAN MICROWAVE - Endang S, Prima; Trisnawati, Trisnawati; Sudiana, I. N. (Jurnal Aplikasi Fisika, 2017)
An experiments have been conducted on the characterization of ceramic silica microstructures extracted from rice husks. The aim of this research is to observe the change of ceramic silica microstructure extracted from rice husk ash after sintered by using microwave. Rice husk ash first extracted using HCl 1M and NaOH 2M, then drying and molding. Ceramic silica is sintered by using microwave and electric furnace at temperature range 1000ËC-1600ËC. Characterization of ceramic silica using scanning electron microscope (SEM). The results of scanning electron microscope (SEM) show that in the sintering process using microwave the surface of silica ceramic sample is form solid granulars andÂ  pores rapidly reduced. While the results of scanning electron microscope (SEM) using the furnace along with rising temperature, showing microstructure ceramic silica samples at each temperature is almost the same but slower pore reduction. Keywords: rice husk, extraction, sintering, microwave, imageJ software, microstructure.Â